Weak acid/bases and pH control in upflow anaerobic sludge bed reactors - Moosbrugger, Richard Engelbert (Department of Civil Engineering, 2016)
Prior to the investigation into H₂CO₃*alkalinity, each waste (substrate) was studied with respect to its potential for pellet formation. During these feasibility studies, the need emerged for a simple, reliable and accurate method to monitor the H₂CO₃*alkalinity and SCFA concentration in the reactor effluent. Against the background described above, the following tasks were set: • Development of a simple method for simultaneous determination of the H₂CO₃*alkalinity (carbonate system alkalinity) and SCFA concentration in anaerobic systems to be used in, (1) assessing the H₂CO₃*alkalinity requirements of different types of wastes when treated in UASB systems, (2) monitoring process stability when treating these wastes under different operating conditions, e.g. different recycle ratios. • Assessment of H₂CO₃*alkalinity requirements for Iauter tun (brewery) waste to maintain a near neutral minimum bed pH in UASB systems. Because this waste generates very little H₂CO₃*alkalinity internally, virtually all H₂CO₃*alkalinity has to be supplied externally. It was of special interest to evaluate the effect of recycling the effluent to the influent in order to recover the effluent H₂CO₃*alkalinity and to dilute the base influent COD to an effective influent COD, CODe, defined as: base influent COD/(1 + recycle ratio). • Assessment of H₂CO₃*alkalinity requirements for wine distillery waste to maintain a near neutral- minimum bed pH in UASB systems. This waste generates a substantial mass of H₂CO₃*alkalinity internally due to deamination of proteins to ammonium/ammonia, reduction of sulfates to sulfides and removal of organic acid salts such as potassium bitartrate. Similar to the Iauter tun waste it was of interest to evaluate the effect of recycling on process performance and on the requirements of H₂CO₃*alkalinity at different recycle ratios, i.e. different CODe concentrations. • Assessment of a pure proteinaceous waste, casein: This substrate provides the opportunity to study the H₂CO₃*alkalinity generation from deamination and the effect of pH changes on process performance of systems with high levels of inorganic nitrogen. With high levels of inorganic nitrogen generated in the reactor liquid due to deamination the likelihood increases of inhibitory effects developing due to increased ammonia (NH₃) levels at higher than neutral pH values. It was of interest to evaluate the effect of pH change on process performance due to the NH₃ inhibition. Because of the differing nature of these tasks each will be dealt with separately, describing the problems encountered and the solutions achieved.